2020
DOI: 10.1097/rlu.0000000000003110
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Receptor Radionuclide Therapy in Patients With Differentiated Thyroid Cancer

Abstract: Purpose As patients with progressive medullary thyroid cancer (MTC) and radioiodine-refractory metastatic differentiated nonmedullary thyroid cancer (DTC) have poor prognoses and present therapeutic challenges, peptide receptor radionuclide therapy (PRRT) targeting the somatostatin receptor provides a promising option. This meta-analysis evaluated the therapeutic effects and outcomes of PRRT in differentiated thyroid cancer. PATIENTS AND METHODS PUBMED,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 73 These early data suggest that PRRT may be considered in selected patients with advanced, progressive, or metastatic MTC in the context of a clinical trial. 72 , 73 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 73 These early data suggest that PRRT may be considered in selected patients with advanced, progressive, or metastatic MTC in the context of a clinical trial. 72 , 73 …”
Section: Resultsmentioning
confidence: 99%
“…The pooled proportion of patients with disease control in MTC was nearly 60% with serious adverse events occurring in 2.79%. 73 These early data suggest that PRRT may be considered in selected patients with advanced, progressive, or metastatic MTC in the context of a clinical trial. 75 This is particularly relevant for patients with Stage-III or -IV disease who have an excellent response to initial therapy.…”
Section: Imagingmentioning
confidence: 99%
“…A meta-analysis by Lee et al. evaluated 11 published articles on DTC and/or MTC for efficacy and outcomes with various PRRTs ( 123 ). The objective response rate (ORR) in MTC was 8.5% (95% CI, 1.9% – 19.2%; i 2 = 53.5%) and the disease control rate (DCR) was 60% (95% CI, 49.6%–69.8%; i 2 = 28.7%), while for DTC, the ORR and DCR rates were 15.6% (95% CI, 7.80%–26.74%; i 2 = 0%), and 53.9% (95% CI: 41.13%–66.39%; i 2 = 0%), respectively.…”
Section: Summary Of Current Literaturementioning
confidence: 99%
“…A meta-analysis study evaluated the therapeutic effect of PRRT in 67 RAI-refractory DTC patients and reported pooled proportions of objective response rate of 15.61%, disease control rate of 53.95%, and serious adverse events of 2.83%. Moreover, PRRT with 177 Lu had a relatively better therapeutic effect than PRRT with 90 Y [ 70 ]. PRRT may become an alternative treatment for recurrent or metastatic RAI-refractory DTC patients with adequate SSTR expression.…”
Section: Non-iodine-related Pet Radiopharmaceuticalsmentioning
confidence: 99%